The Relationship Of Knowledge And Attitude Of Mother’s Breasfeeding With Exclusive Giving - Monifa Putri; Deni Listi (JURNAL PROTEKSI KESEHATAN, 2020)
Breast milk (ASI) is the only food that is the best for babies, because it has themost complete nutritionalcomposition for baby’s growth and development.Methode: this research is analytic using cross sectional approach. The samplingtechnique is by simple random sampling. Data analysis was performed using theChi-Square test at a significance level of p<0.05. Result: the study showed thatfrom 68 respondents the majority of knowledge of breastfeeding morthers withexclusive breastfeeding was well-informed 48 people (70.6%) and the ChiSquare statistical test results obtained a P value of <0.05 (P. Value = 0.004).Breastfeeding with exclusive breastfeeding the majority of positive attitude 57people (83.8%) and the Chi-Square statistical test results obtained a value ofP<0.05 (P. Value=0.008). Conclusion: based on the results of the study showeda significant relationship between knowledge (P. Value=0.004) and attitude (P.Value=0.008) towards exclusive breastfeeding.